2020
DOI: 10.1371/journal.pone.0230563
|View full text |Cite
|
Sign up to set email alerts
|

Morphine exposure exacerbates HIV-1 Tat driven changes to neuroinflammatory factors in cultured astrocytes

Abstract: Despite antiretroviral therapy human immunodeficiency virus type-1 (HIV-1) infection results in neuroinflammation of the central nervous system that can cause HIV-associated neurocognitive disorders (HAND). The molecular mechanisms involved in the development of HAND are unclear, however, they are likely due to both direct and indirect consequences of HIV-1 infection and inflammation of the central nervous system. Additionally, opioid abuse in infected individuals has the potential to exacerbate HIV-comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…2 ). Although 2–14 days of morphine and Tat/HIV co-exposure typically exacerbates cytokine production, gliosis, and bystander neuronal injury in vitro [ 30 , 37 , 43 , 166 ] and in vivo [ 29 , 38 ], 3 months of Tat induction elicited a far less fulminant morphine-dependent interactive pathology. Morphine and Tat co-exposure elevated 3-NT in microglia, but failed to increase microglial numbers as seen previously following 48 h or 12-day Tat induction [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Although 2–14 days of morphine and Tat/HIV co-exposure typically exacerbates cytokine production, gliosis, and bystander neuronal injury in vitro [ 30 , 37 , 43 , 166 ] and in vivo [ 29 , 38 ], 3 months of Tat induction elicited a far less fulminant morphine-dependent interactive pathology. Morphine and Tat co-exposure elevated 3-NT in microglia, but failed to increase microglial numbers as seen previously following 48 h or 12-day Tat induction [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, neurological involvement is observed is the vast majority of HIV-coinfected patients (Ferreira et al, 1997;Cordova et al, 2008). Astrocytes have been proposed as parasite (Weinkauf et al, 2011;Silva et al, 2015Silva et al, , 2017, and also HIV target cells, as we and others have reported (Urquiza et al, 2017;Chen et al, 2020;Li et al, 2020;Proust et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, Balinang et al also demonstrated increased HIV replication in neural progenitor cells in the presence of morphine [53]. Notably, HIV proteins also synergize with morphine to increase the expression of opioid receptors, alter cell cycle regulation, and exacerbate neurotoxicity and neuroinflammation [54][55][56][57][58][59][60].…”
Section: Opioids and Hivmentioning
confidence: 99%
“…Additionally, Balinang et al also demonstrated increased HIV replication in neural progenitor cells in the presence of morphine [53]. Notably, HIV proteins also synergize with morphine to increase the expression of opioid receptors, alter cell cycle regulation, and exacerbate neurotoxicity and neuroinflammation [54][55][56][57][58][59][60]. Using an in vitro HIV-CD4+ T cell system, Liang et al showed that morphine treatment induced more drug-resistant mutations under selective pressure from antiretroviral drugs and shortened the generation time for such mutations compared to controls treated with only antiretroviral drugs [61].…”
Section: Opioids and Hivmentioning
confidence: 99%